The Social Function of Cooking Structures during the Neolithic. A View from the Central Mediterranean - Conati Barbaro, Cecilia (Food & History, 2021)
Abstract Fire structures such as ovens, hearths and cooking pits occur quite frequently in Neolithic settlements, inside or outside dwellings. According to their location, they can be associated with communal or individual activities, often connected with food processing and cooking. Beyond their utilitarian function, these structures embody a strong symbolic value. This article aims to examine ovens and fire pits found in several Italian Neolithic sites and to understand their social role in Neolithic communities. In this regard, the construction materials and techniques, the type of fuel, the presence of additional features, the location of these facilities within settlements will be discussed. Abstract Les structures de feu, telles que les fours, les foyers et les fosses de cuisson, sont relativement fréquentes dans les établissements néolithiques, à l’intérieur ou à l’extérieur des habitations. Selon leur emplacement, elles peuvent être associées à des activités collectives ou individuelles, souvent liées à la transformation des aliments et à la cuisson. Au-delà de leur fonction utilitaire, ces structures revêtent une forte valeur symbolique. Cet article vise à examiner les fours et les foyers trouvés dans plusieurs sites néolithiques italiens et à comprendre leur rôle social au sein des communautés néolithiques. À cet égard, seront discutés les matériaux et techniques de construction, le type de combustible, la présence d’éléments supplémentaires, l’emplacement de ces installations au sein des établissements.